(untitled) (Modern education and development, 2025)
The rapid expansion of big data necessitates advanced analytical approaches to extract meaningful insights. Data mindsighting, a novel concept integrating cognitive analytics, artificial intelligence (AI), and predictive modeling, plays a critical role in understanding and interpreting massive datasets. This paper explores the role and importance of data mindsighting in big data theory, its methodologies, applications, and future prospects.